-2(5-2k)=3(1+2k)

Simple and best practice solution for -2(5-2k)=3(1+2k) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(5-2k)=3(1+2k) equation:


Simplifying
-2(5 + -2k) = 3(1 + 2k)
(5 * -2 + -2k * -2) = 3(1 + 2k)
(-10 + 4k) = 3(1 + 2k)
-10 + 4k = (1 * 3 + 2k * 3)
-10 + 4k = (3 + 6k)

Solving
-10 + 4k = 3 + 6k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-6k' to each side of the equation.
-10 + 4k + -6k = 3 + 6k + -6k

Combine like terms: 4k + -6k = -2k
-10 + -2k = 3 + 6k + -6k

Combine like terms: 6k + -6k = 0
-10 + -2k = 3 + 0
-10 + -2k = 3

Add '10' to each side of the equation.
-10 + 10 + -2k = 3 + 10

Combine like terms: -10 + 10 = 0
0 + -2k = 3 + 10
-2k = 3 + 10

Combine like terms: 3 + 10 = 13
-2k = 13

Divide each side by '-2'.
k = -6.5

Simplifying
k = -6.5

See similar equations:

| -6y+9=-7y | | 2sinx-2cosx= | | 3y-9=y+5 | | 6-2x-x-3-7x= | | -x=132 | | c=3.14(28) | | j^2-14j+48= | | y^3-2y^2-3y+10=0 | | -2(n+7)=-8-n | | 0.5(x-3)+1.4=10 | | p-3=3p+5 | | 2X^5-3xy= | | 1+3t=4 | | c^2-18c+32= | | -2x+4=-7(x+3) | | 13x-8=88 | | 3w^2+w+1=0 | | 8+7p=-6+5p | | -x^2-20x+80=0 | | y+(-7)=9 | | N^2-20n+12=0 | | -9t-10+8t=-3t+10 | | 4(x-6)-4=20 | | 3x+2y=45.03 | | -20=15g-5 | | -9y=7.65 | | 5a+4b=16 | | d^2+5d+4= | | 50(0.98)=50 | | 2w+1+18=w-1 | | 8x-9y=10 | | x-7=4.45 |

Equations solver categories